Adaptation and initial examination of the psychometric properties of the Short Supervisory Relationship Questionnaire (SSRQ) for use with general practice registrars. Issue 6 (1st November 2020) - Costello, Shane; Benson, Jill; Burns, Joan; Bentley, Michael; Elliott, Taryn; Kippen, Rebecca
ABSTRACT: The relationship between general practice (GP) registrars and their supervisors underpins the training experience for the next generation of medical practitioners. Building on recent research into the development and validation of a measure of the relationship between registrars and supervisors from the perspective of the supervisor, the current study focuses on the educational alliance from the perspective of the registrar. This paper presents an adaptation and initial validation of the clinical psychology supervisory relationship measure for GP registrars in an Australian context. Following an Expert Group review and adaptation of the items, 238 GP registrars completed the adapted tool. Using exploratory factor analysis and Procrustes confirmatory rotation, an optimal four factor model of the supervisory relationship was identified, reflecting measures of Safe base ( α =.93), Supervisor investment ( α =.96), Registrar professionalism ( α =.90), and Emotional intelligence ( α =.87). The general practice supervisory relationship measure for registrars (GP-SRMR) demonstrated excellent model fit, high internal consistency, and was theoretically consistent with the original tool. Implications for clinical education and future research are presented.